Modifications of cognitive and motor tasks affect the occurrence of event-related potentials in the human cortex - Rektor, Ivan; Brázdil, Milan; Nestrašil, Igor; Bareš, Martin; Daniel, Pavel (European journal of neuroscience, 2007)
This study concerns the question of how task modification affects the frequency occurrence of event-related potentials (ERP) inside the active cortical areas. In 13 candidates for epilepsy surgery, 156 sites in the temporal (74), frontal (73), and parietal (9) cortices were recorded by means of depth and subdural electrodes. Four modifications of the somatosensory evoked P3-like potentials were performed; (i) an oddball paradigm with silent counting of target stimuli (P3c); (ii) an oddball paradigm with a hand movement in response to target stimuli (P3m); (iii) an S1-S2 paradigm, ERP in the P300 time window after the S2 stimulus, with silent counting of target stimuli (S2c), and (iv) an S1-S2 paradigm with a hand movement in response to target stimuli (S2m). In comparing the oddball paradigms with the S1-S2 (contingent negative variation, CNV) paradigms, four regions emerge that are significantly linked with the oddball P3; the prefrontal cortex, the cingulate, the amygdalo-hippocampal complex, and the lateral temporal cortex. A prominent role of the cingulate and the fronto-orbital cortex in the cognitive processing of movement was supported when tasks with identical cognitive loads but different required responses were compared. Even relatively simple cognitive tasks activate many cortical regions. The investigated areas were activated in all tests; however, small regions in each field were active or inactive in relation to the nature of the task. The study indicates a variable and task-dependent internal organization of a highly complex and widely distributed system of active cortical areas.
Keywords: financování organizované; Dose-Response Relationship, Radiation; Electroencephalography; kontingentní negativní variace; Psychomotor Performance; Cognition; kognitivní evokované potenciály P300; Contingent Negative Variation; mladiství; Hand; Brain Mapping; mužské pohlaví; vztah dávky záření a odpovědi; elektroencefalografie; Adult; ruka; psychomotorický výkon; Mental Processes; kognice; Financing, Organized; mozková kůra; ženské pohlaví; Event-Related Potentials, P300; Humans; mapování mozku; duševní procesy; Cerebral Cortex; elektrická stimulace; dospělí; Female; Electric Stimulation; Adolescent; lidé; Male